Rectal indometacin dose escalation for prevention of pancreatitis after endoscopic retrograde cholangiopancreatography in high-risk patients: a double-blind, randomised controlled trial. (February 2020) - Fogel, Evan L; Lehman, Glen A; Tarnasky, Paul; Cote, Gregory A; Schmidt, Suzette E; Waljee, Akbar K; Higgins, Peter D R; Watkins, James L; Sherman, Stuart; Kwon, Richard S Y; Elta, Grace H; Easler, Jeffrey J; et al.
Summary: Background: Although rectal indometacin 100 mg is effective in reducing the frequency and severity of pancreatitis after endoscopic retrograde cholangiopancreatography (ERCP) in high-risk patients, the optimal dose is unknown, and pancreatitis incidence remains high. The aim of this study was to compare the efficacy of two dose regimens of rectal indometacin on the frequency and severity of pancreatitis after ERCP in high-risk patients. Methods: In this randomised, double-blind, comparative effectiveness trial, we enrolled patients from six tertiary medical centres in the USA. Eligible patients were those at high risk for the development of pancreatitis after ERCP. We randomly assigned eligible patients (1:1) immediately after ERCP to receive either two 50 mg indometacin suppositories and a placebo suppository (standard-dose group) or three 50 mg indometacin suppositories (high-dose group). 4 h after the procedure, patients assigned to the high-dose group received an additional 50 mg indometacin suppository, whereas patients in the standard-dose group received an additional placebo suppository. The randomisation schedule, stratified according to study centre and with no other restrictions, was computer generated by an investigator who was uninvolved in the clinical care of any participants, distributed to the sites, and kept by personnel not directly involved with the study. These same personnel were responsible for packaging the drug and placebo in opaque envelopes. Patients, study personnel, and treating physicians were masked to study group assignment. The primary outcome of the study was the development of pancreatitis after ERCP. Analyses were done on an intention-to-treat basis. This trial is registered with ClinicalTrials.gov, number NCT01912716, and enrolment is complete. Findings: Between July 9, 2013, and March 22, 2018, 1037 eligible patients were enrolled and randomly assigned to receive either standard-dose (n=515) or high-dose indometacin (n=522). Pancreatitis after ERCP occurred in 141 (14%) of 1037 patients—76 (15%) of 515 patients in the standard-dose indometacin group and 65 (12%) of 522 patients in the high-dose indometacin group (risk ratio [RR] 1·19, 95% CI 0·87–1·61; p=0·32). We observed 19 adverse events that were potentially attributable to study drug. Clinically significant bleeding occurred in 14 (1%) of 1037 patients—six (1%) of 515 patients in the standard-dose indometacin group and eight (2%) of 522 patients in the high-dose indometacin group (p=0·79). Three (1%) of 522 patients in the high-dose indometacin group developed acute kidney injury versus none in the standard-dose group (p=0·25). A non-ST elevation myocardial infarction occurred in the standard-dose indometacin group 2 days after ERCP. A transient ischaemic attack occurred in the high-dose indometacin group 5 days after ERCP. All 19 adverse events, in addition to the 141 patients who developed pancreatitis after ERCP, were considered serious as all required admission to hospital. We observed no allergic reactions or deaths at 30 day follow-up. Interpretation: Dose escalation to rectal indometacin 200 mg did not confer any advantage compared with the standard 100 mg regimen, with pancreatitis incidence remaining high in high-risk patients. Current practice should continue unchanged. Further research should consider the pharmacokinetics of non-steroidal anti-inflammatory drugs to determine the optimal timing of their administration to prevent pancreatitis after ERCP. Funding: American College of Gastroenterology.